2018
DOI: 10.1007/s12035-018-1207-5
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Claudin-11 in Disruption of Blood-Brain, -Spinal Cord, and -Arachnoid Barriers in Multiple Sclerosis

Abstract: It is important to understand the molecular mechanisms of barrier disruption in the central nervous system (CNS) of patients with multiple sclerosis (MS). The purpose of the present study was to clarify whether claudin-11 is involved in the disruption of two endothelial barriers (blood-brain barrier (BBB) and blood-spinal cord barrier (BSCB)) and two epithelial barriers (blood-arachnoid barrier (BAB) and blood-CSF barrier (BCSFB)) in the CNS in MS. Immunohistochemical analysis revealed that, in both normal hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 31 publications
0
67
0
Order By: Relevance
“…Huang et al (2017) showed similar alterations in BBB permeability, and claudin-5, occludin, and ZO-1 expression levels in cerebellar white matter could be prevented by a Kv1.3 channel blocker in EAE rats (Huang et al, 2017). Claudin-11 protein expression has also been shown to be significantly downregulated in MS patients and in EAE (Uchida et al, 2019). Differences in TJ alteration data between different groups may be due to differences in the specific EAE model, the time points examined, or the tissue in which the analysis was performed.…”
Section: Multiple Sclerosismentioning
confidence: 78%
See 1 more Smart Citation
“…Huang et al (2017) showed similar alterations in BBB permeability, and claudin-5, occludin, and ZO-1 expression levels in cerebellar white matter could be prevented by a Kv1.3 channel blocker in EAE rats (Huang et al, 2017). Claudin-11 protein expression has also been shown to be significantly downregulated in MS patients and in EAE (Uchida et al, 2019). Differences in TJ alteration data between different groups may be due to differences in the specific EAE model, the time points examined, or the tissue in which the analysis was performed.…”
Section: Multiple Sclerosismentioning
confidence: 78%
“…Claudin-1 has been detected at the BBB at the messenger RNA (mRNA) level (Winkler et al, 2020); however, its expression at the BBB remains controversial in part due to possible antibody cross-reactivity between claudin-1 and claudin-3 (Bauer et al, 2014). Claudin-11 and claudin-12 have also been detected at the BBB, but claudin-12 is likely not important for barrier function (Castro Dias et al, 2019;Uchida et al, 2019).…”
Section: Molecular Composition and Regulation Of Tjs At The Bbbmentioning
confidence: 99%
“…50) Furthermore, the direct interaction of CD9 with a tight junctionrelated protein claudin-1 was demonstrated by means of a cross-linking proteomics study. 51) We have recently reported that claudin-5 and claudin-11 are expressed at the human and rodent BBB. 52) Although it is unclear whether CD9 interacts with claudin-5 or claudin-11 at the BBB, these results imply that reduced expression of CD9 may affect the integrity of endothelial cell-to-cell junctions.…”
Section: Discussionmentioning
confidence: 98%
“…While the importance of claudin-5 as a tight junction protein at the cerebral endothelium is widely recognized [59], the potential role of other claudins [60] is more contentious. Uchida et al [61] recently provided evidence in multiple sclerosis that claudin-11 is decreased at the BBB (and the blood-spinal cord and the blood-arachnoid barriers) contributing to barrier leakiness. In contrast, Castro Dias et al [62,63] found that loss of claudin-12 and claudin-3 had no effect on BBB permeability in mice and that claudin-3 was absent from the cerebral endothelium.…”
Section: Claudins At the Cerebral Endotheliummentioning
confidence: 99%